Peningkatan Kesadaran Masyarakat Sekolah melalui Edukasi Anti Perundungan dan Kekerasan Seksual di Sekolah SMK Muhammadiyah 04 Boyolali: Penelitian - Muhammad Ramdhani; Muhammad Reza Adani; Nur Kholis Majid; Muhammad Reyza Daffi Reo Saputra (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Bullying and sexual violence in school environments remain critical issues that directly affect students’ mental health, learning comfort, and character development. The lack of students’ understanding regarding the forms, impacts, and reporting mechanisms of such violence increases the risk of its occurrence. This study aims to enhance school community awareness through educational programs on anti-bullying and sexual violence at SMK Muhammadiyah 04 Boyolali. The method used is a participatory counseling approach through lectures, interactive discussions, and case studies involving students and educators. The results show a significant improvement in students’ understanding of bullying behaviors, types of sexual violence, and the importance of reporting and maintaining mutual safety. The educational program also increased students’ confidence to speak up, creating a safer and more comfortable school environment. In conclusion, anti-bullying and sexual violence education is proven effective as a preventive effort to build collective awareness within the school community.